Implementasi Kombinasi Model PBL, AIR, TIME TOKEN Muatan Ppkn Kelas 5 SDN Bata Kabupaten Balangan - Annisa Syafarina; Ramadi (CV. ITTC INDONESIA, 2023)
The problem of this research is that students are still lacking in critical, rational and creative thinking, lack of students in participating actively and responsibly in learning and problem solving, lack of enthusiasm of students in expressing opinions and responses, students still experience learning difficulties, especially in PPKn content because learning is less interesting and fun and less meaningful and creative for students, is one-way. The purpose of this study was to describe teacher activities, increase student activity and learning outcomes. This study uses a qualitative approach. The data taken is qualitative data obtained through observing teacher activities and student activities, then using quantitative data for student learning outcomes obtained through individual written tests. The research results showed that teacher activity in cycle 1 reached a score of 25 with the